Social Media Management Strategies of Islamic Boarding Schools in Enhancing Public Trust - Madinatul Munawaroh; Malikul Habsi (DAAR EL-IDARAH: Journal of Islamic Education Management, 2025)
This study examines social media management strategies employed by Islamic boarding schools (pesantren) in enhancing public trust. As pesantren increasingly engage with digital platforms, social media has become a vital tool for branding, transparency, and communication with stakeholders. Using a qualitative approach through literature review and case analysis, this research identifies key strategies such as consistent content creation, value-based messaging, and interactive engagement with audiences. The findings reveal that effective social media management not only improves the public image of pesantren but also strengthens trust by showcasing accountability, educational achievements, and community service. Moreover, challenges such as limited digital literacy and resource constraints are highlighted as factors that need to be addressed. This study contributes to the understanding of how pesantren can optimize social media to build credibility, foster community relations, and sustain institutional development in the digital era.